Vocational education & training students’ families’ expectations about their future employment - Garcia-Gomez, Soledad; Ordonez-Sierra, Rosario; Vinuesa Mariscal, Esther; Izquierdo Chaparro, Rosario (Education Policy Analysis Archives, 2016)
This paper is part of a qualitative research focused in vocational education & training (VET) about the expectations of students’ families on their future employment. It has been accepted till not so long that VET was the best way to get a job quickly. The current economic crisis may has altered this belief. So that we have interviewed some families from the South of Spain to better know what they think about their children’s decisions of being enrolled in VET. The data content analysis shows that they agree with their children academic choices (VET), and that they are worried about their future access to an employment. They criticize current politics and disagree with young people emigrating to other countries in order to get a better job.